(3GdPNjQI GdNhGQR eTGgjIs - (3CHh EHQGgje , ESeGYjd Hf GdMSf GdMSjfj GdLQLGfj,J (B531 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GYdehG Cfi HYO HdhZi GdSHYjf ef YeQi LeYJ HNhGQReTGgjI aj GdWH HGddZI GdYLejI , hHYO aQGZi efg hLOJ cd ef fXQ Pdc GdcJGH jJCSa Ydjg hjbhd (B: (3djJc LeYJ gPG GdcJGH s
(3BNQgG (B:s
(3BNQ eHJhQ , hBNQ eGajg (B: (3adPdc jfHZi Gf jfbU NUH GdHOf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B97 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B308s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs